(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Organizations must recognize that they face real problems and prioritize them in order to preserve their human resources. Managers should pay special attention to all HR functions that play an important role in various organizations. This is especially important in coaching and mentoring conversations to help employees meet their quotas. Quality work: As stated in the questionnaire survey, strategies for mentoring and coaching in terms of Quality work are effective in the employees’ workplace. It helps the employees to produce quality work, avoiding distraction and digression, ranked by employees to the top to a very great extent. Mentor Training: set clear expectations and goals at the beginning of the relationship strategy that is effective for coaching and mentoring, resulting in the employee survey questionnaire. The researchers recommend that the company should have a celebration of the accomplishments at the end of the week for productivity and their recognition of the effort of the employee as the result of the salary increase. Make a goals road map as a plan and schedule for the training of the employees to be effectively evaluated for them to make quality work.